A transmittive type broadband cross polarization converter for mid wavelength infrared region - Nandi R.; Nilotpal; Bhattacharyya S. (My University, 2025)
A broadband transmittive type cross polarization converter (CPC) for the mid infrared frequency band is reported in this paper. The proposed CPC structure converts an incident linearly polarized wave to cross polarized wave over a wide frequency band extending from 24 THz to 49 THz; thus behaving as a wide band converter of bandwidth 25 THz. The structure exhibits a high polarization conversion ratio (PCR) of more than 80% for the complete operating frequency band. A PCR of more than 90% is obtained between two frequency bands extending from 39.35 THz to 47.9 THz and 24.83 THz to 26.75 THz. The structure is further studied for oblique incidence response where it maintains broadband cross polarization conversion up to 40° for both TE and TM polarizations. The structure acts as a transmittive CPC up to 30° polarization angle. The structure is compact in thickness (∼ λ/5) as well as periodicity (∼ λ/5) with respect to lower frequency of polarization conversion bandwidth. © 2019 URSI. All rights reserved.